The situation of female immigrants on the German labour market: A multi-perspective approach - Zerrin Salikutluk; Johannes Giesecke; Martin Kroh (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
While general ethnic disadvantages are well documented, much less is known about coinciding disadvantages of ethnic origin and gender. Based on theoretical arguments of human capital theory, sociocultural approaches, labour market segmentation theory, and discrimination mechanisms, we investigate whether immigrant women experience more difficulties on the labour market than immigrant men, non-immigrant men and women. Using data from the German Socio-economic Panel from 2013 and 2015 we deal with interaction patterns of ethnic origin and gender regarding various labour market outcomes for immigrants from Turkey and the former Soviet Union. We analyse the impact of individual resources like education, language proficiency, and job characteristics on ethnic and gender gaps. We find evidence of additional disadvantages of immigrant women on each outcome variable that largely seem to be attributable to differences in qualifications and language proficiency. However, for women from the former Soviet Union and second-generation Turkish women specific disadvantages are apparent that cannot be explained by individual and job characteristics.
Keywords: 330; Labour market; Integration; Migration; Gender; Gender disparities